Adjuvant treatment for breast cancer. Issue 2 (February 2022) - Latif, Jasima; Mehta, Shaveta
Abstract: The primary treatment for early breast cancer (EBC) is surgery. Adjuvant treatments, including systemic treatments and radiotherapy after surgery, have shown to reduce local and distant relapse, resulting in improved survival in breast cancer (BC). Multiple components of the clinical and histopathological characteristics can be used to risk stratify patients and are helpful in decision making about adjuvant treatments. Recent advances in both systemic treatments and radiotherapy techniques have led to more personalized treatment for patients with the aim to reduce BC mortality and improve quality of life long term.